A multicenter randomized clinical trial with a novel decision support tool to improve IVF success - Urmila Diwekar; Nihar Ranjan Bhoi; Shyam Nandan Gupta; Anjali Sharma; Sumitra Hota; Amol Subhash Lunkad; Simmi Arora; Sunita Kumari; Amol Naik; Tanu Batra; Sasmita Naik; Akanksha Jangid; et al. (Reproduction and Fertility)
A small multi-center trial indicated that using a clinical decision support tool, Opt-IVF, to guide follicular-stimulating hormone (FSH) dosing during superovulation increased the number of high-quality embryos in non-PCOS patients treated with an antagonist protocol. This clinical trial aims to study whether Opt-IVF improves clinical pregnancy rates across all patient types and protocols without any exceptions. 402 women aged 25–45 undergoing in vitro fertilization (IVF) were enrolled in the trial. Half (201 women) were randomly assigned to the intervention group (Opt-IVF) to guide FSH dosing and determine the antagonist and trigger days. The other half was assigned to the control group (conventional treatment). The participants in the intervention group required significantly lower cumulative FSH doses during their controlled ovarian stimulation cycles. This group also had a higher number of M2 oocytes retrieved compared to the control group. Furthermore, the intervention group produced a significantly higher number of embryos and good-quality blastocysts, leading to increased pregnancy rates compared to the control group. We conclude that using the Opt-IVF clinical decision support tool led to numerous benefits, such as reducing the need for ultrasound examinations after day 5, lowering the required FSH dosage, and achieving a higher number of high-quality blastocysts and increased pregnancy rates. Thus, Opt-IVF offers a personalized, optimized, and simplified approach to superovulation.